The Impact of Direct and Indirect Taxes on Economic Growth: An Empirical Study in Albania: Array - Korbi, Alban; Zani, Blisard (Journal of Danubian Studies and Research, 2021)
Directly or indirectly, fiscal framework and fiscal changes in overall have an important impact in the economic growth. This paper aims to analyze the impact of direct and indirect taxes (administered by tax authorities and customs) in the gross domestic product, based in an econometric model of autoregressive vectors (VAR) model. We have used data for Albanian GDP and tax revenues for the time series starting in 1993 up to 2020. The model uses three endogenous variables, direct tax revenues, indirect tax revenues and gross domestic products. Based on the analysis in this paper, it can be seen that the main impact is given by direct tax revenues and the previous year economic growth itself. Meanwhile, indirect tax revenues tend to have no significant impact in the economic growth for the years taken into consideration in this paper. This analysis serves for proper orientation of fiscal policies and the changes in fiscal legislation from time to time to maximize the role and effects of tax revenues in economic growth. In addition, this paper aims to encourage a public discussion about the important role of fiscal policy in economic growth.